Abciximab in rescue therapy of thromboembolic events during endovascular treatment of cerebral aneurysms: single center experience of 49 cases - Lukas Lenhart; Valentin Ladenhauf; Verena Rass; Stephanie A. Treichl; Ronny Beer; Christian F. Freyschlag; Elke R. Gizewski; Astrid E. Grams (Frontiers in Neurology, 2025)
BackgroundThe aim of this study was to assess the safety and effectiveness of abciximab (ReoPro®), a glycoprotein-IIb/IIIa receptor antagonist, in the management of thromboembolic complications during endovascular treatment of intracranial aneurysms.MethodsFrom an inhouse data base of 218 coil embolisations in 178 patients with cerebral aneurysms (median age 57 years, 72% females)–among them 53 interventions with subarachnoid hemorrhage (SAH) requiring acute endovascular treatment, and 165 with elective endovascular treatment of unruptured aneurysms - we retrospectively reviewed 53 interventions that received abciximab during endovascular treatment, and diffusion-weighted imaging after endovascular treatment (median 7 days after intervention, range 5 to 9 days). Four subgroups were identified, (i) SAH patients with abciximab (SAH-Ab, n = 18), (ii) SAH patients without abciximab (SAH-no, n = 35), (iii) elective patients with abciximab (El-Ab, n = 31), and (iv) elective patients without abciximab (El-no, n = 134) treatment. Angiographic success of clot dissolution, post-interventional occurrence of intracranial hemorrhages and the modified Rankin Scale (mRS) pre and 6 months after endovascular treatment were recorded. Brain tissue infarction-load was categorized as: no, punctual (<500 mm2), small (500–1,000 mm2) and large (>1,000 mm2) infarctions.ResultsComplete and partial angiographic success was achieved in 94% of cases. No significant differences in infarction-loads were found between SAH-Ab and SAH-no, or El-Ab and El-no subgroups. Abciximab use was not associated with increased infarction-loads or worse mRS scores. Hunt & Hess score at admission significantly predicted both infarction-loads (β = 0.38, p = 0.02) and 6-month mRS (β = 0.75, p < 0.001) in SAH patients. Two patients experienced post-interventional hemorrhages: one small bleed near the extraventricular drain in in the SAH-Ab group, and one large hemorrhage due to wire perforation in the El-Ab group. No fatal hemorrhages occurred following abciximab administration.DiscussionAbciximab was safe and seemed effective for the management of thromboembolic complications during endovascular treatment of intracranial aneurysms, without increasing infarct burden or compromising functional outcomes in affected patients.